Alterações neuropsiquiátricas na doença de Parkinson - Arthur Melo e Kummer (2009)
Parkinsons disease (PD) is clinically defined by its motor signs. Nevertheless, non-motor symptoms are very frequent and probably more impairing than the motor signs. These symptoms are seldom recognized and often inadequately treated. They worsen the quality of life, complicate the treatment of motor signs and are predictors of a bad prognosis. The main objective of this study was to evaluate the frequency and severity of psychiatric disorders and other behavioral changes in PD. A structured interview (Mini-Plus) was used to study neuropsychiatric disorders, as well as several instruments assessing depressive and anxiety symptoms, fatigue and sleep scales, brief cognitive batteries and some specific questionnaires about uncommon behavioral changes such as dopamine dysregulation syndrome and punding. We observed a high frequency of psychiatric disorders, but there was no statistical difference with regard to age of disease onset. Social anxiety disorder occurred in 50% of participants, and it was associated with depression and anxiety. Major depression occurred in nearly a third of the sample. Death ideas and suicidal ideations are common in PD, but suicide attempts are rare. Nearly 65% of patients had loss of libido. In PD, depressive symptoms are the main predictor of loss of libido, but female gender and advanced age are also relevant. We observed that patients with PD present cognitive impairments even at initial stages of disease. Depression impaired executive functioning, especially in those patients with low educational level. Nearly half of the patients suffer from clinically significant fatigue. Female gender, depressive symptoms and daytime sleepiness are predictors of fatigue. In conclusion, neuropsychiatric disorders are very frequent in PD. It is of great clinical and theoretical importance to study these disorders, contributing to the comprehension of these syndromes beyond the context of PD.